Armastus, Andestus, Alandlikkus: The Rediscovery of the Orthodox Christianity in Post-Soviet Estonia - Milena Benovska-Sabkova (Journal of Ethnology and Folkloristics)
The aim of the present article is to outline some of the basic characteristics of the post-Soviet ‘renaissance’ of the Estonian Apostolic Orthodox Church (under jurisdiction of the Ecumenical Patriarchate of Constantinople), for example the conversion from Lutheranism to Orthodox Christianity and the processes of rediscovery, reinvention and ‘Estonianisation’ of Orthodox Christianity. The restoration of the autonomous Estonian Apostolic Orthodox Church, beginning in the 1990s, is due to the historic presence of Orthodoxy in Estonia, but also has the particularities of a new project that seeks contemporary horizons and copes with specific postsocialist problems. The paper takes a closer look at the specific dimensions of these processes through a study of a small Orthodox community: the parish of St. Alexander Nevsky church in Tartu. The author strives to demonstrate the living process of reinvention of Orthodox Christianity in Estonia and more generally the ‘making’, creation, of religion. The small religious community in Tartu dealt with in the paper, shares a number of features of the transforming religiosity of Europe: emphasis on spirituality, openness to the impacts of globalisation, the hybrid character of certain religious practices. It is likewise an example of the fact that Orthodox Christianity may also be the free choice of people looking for moral perfection. This is one of the answers to the main research question about the reasons and character of a contemporary conversion to Orthodox Christianity.